The age of television : experiences and theories - Buonanno, Milly (Intellect Books, 2008)
At a stage of major change in the world of television (the coming of digital TV, multiple channels, mobile TV on cellphones) this book seeks to take stock of the impact of the advent and presence of television on daily life over the past fifty years, or slightly longer. The author takes as her standpoint, or rather places at the centre of her analysis and considerations, the human experience and the way in which the medium of television has radically changed it. Connection; mobility; plurality. The discourse developed in the various chapters of the book focus on this triad of conceptual catego.